Relations Between Atherogenic Index of Plasma, Ratio of Small Dense Low Density Lipoprotein/Lecithin Cholesterol Acyl Transferase and Ratio of Small Dense Low Density Lipoprotein/Cholesteryl Ester Transfer Protein of Controlled and Uncontrolled Type 2 DM - Ellis Susanti; Marsetio Donosepoetro; Gatot Susilo Lawrence (The Indonesian Biomedical Journal, 2009)
BACKGROUND: Patients with Diabetes Melitus are proven to be prone to atherosclerosis and coronary heart disease, especially type 2 Diabetes Melitus (T2DM) patient who have higher risk and mortality for cardiovascular risk factor. The Dyslipidemia condition is very common in T2DM as one of the risk factors. Diabetic dyslipidemia is marked by the increased triglyceride (TG), low HDL cholesterol (HDL-C), and increased small dense LDL and apolipoprotein B. Therefore the aim of this study is to assess the differential and correlation between Atherogenic Index of Plasma (AIP), ratio of small dense low density lipoprotein (sdLDL)/lecithin cholesterol acyl transferase (LCAT) and ratio of sdLDL/cholesteryl ester transfer protein (CETP) of controlled and uncontrolled T2DM.METHODS: This study was observational with cross sectional design. In total of 72 patients with T2DM consist of 36 controlled and 36 uncontrolled, participated in this study. The serum TG, HDL-C, sdLDL, LCAT and CETP were examined in their relationship with to T2DM risk.RESULTS: The results of the study indicate that the AIP (p<0.001) increase controlled and uncontrolled T2DM and the ratio of sdLDL/CETP (p=0.004), odds ratio of AIP was 4 (95% CI : 1.501-10.658) and odds ratio of sdLDL/CETP ratio was 4 (95% CI : 1.501-10.658) in uncontrolled T2DM.CONCLUSION: This study showed that the AIP and ratio of small dense LDL/CETP had a significant correlation with the uncontrolled T2DM. The AIP and ratio of small dense LDL/CETP increase was found at the uncontrolled T2DM to be 4 times greater than the controlled T2DM.KEYWORDS: T2DM, atherosclerosis, atherogenic index of plasma, small dense LDL, LCAT, CETP, ratio of sdLDL/LCAT, ratio of sdLDL/CETP